Pilot study to assess the presence of Chlamydia trachomatis in urine from 18-30-year-old males using EIA/IF and PCR. Issue 1 (1st January 2002) - Basarab, Adriana; Browning, David; Lanham, Stuart; O'Connell, Susan
Abstract : Context: To increase detection, urine samples from young males could be opportunistically tested for Chlamydia trachomatis . Objective: To determine C. trachomatis prevalence in urine, optimum specimen and compare sensitivity/feasibility of routine use of different testing methods. Design: Group A, 'sterile' pyuria samples June 1998-January 1999, tested by enzyme immunoassay (EIA) and, if reactive, by immunofluorescence (IF). Subsequently batch-tested by polymerase chain reaction (PCR). Group B, consecutive urine samples October 1998-January 1999; batch-tested by PCR. Setting: Microbiology laboratory. Samples: From males aged 18-30 years; group A = 71, group B = 83. Main outcome measures: Chlamydia trachomatis positive if EIA- and IF- or PCR-positive. Results: Group A: 12 EIA/IF-positive; 9/12 and 15 EIA-negative samples PCR-positive. Group B: 11 PCR-positive; 8/11 showed 'sterile' pyuria. Conclusions: Opportunistic testing of urine from young men shows a significant number of C. trachomatis infections. 'Sterile' pyuria samples are optimal. EIA/IF are less sensitive than PCR but can be routinely performed and detect a significant proportion of cases.